1999
DOI: 10.1046/j.1432-1327.1999.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and possible functions of a trypsin inhibitor of Bombyx mori

Abstract: A protein with a low molecular mass of 6027 was purified from cocoon shell of silkworm, Bombyx mori. Twodimensional polyacrylamide gel electrophoresis (2D/PAGE) resolved this protein into a single spot with pI 4.3 and M r 6000. Amino acid sequence analysis revealed that this protein consists of 55 amino acids, six of these being cysteine residues and is highly homologous to bovine pancreatic trypsin inhibitor-type inhibitors. The 6-kDa protein is heat stable and acid stable and inhibits bovine trypsin by formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…They are designated cocoon shell-associated trypsin inhibitors (CSTIs). 36) Although the physiological role of CSTI is not fully known, it has been suggested that it plays a significant role in biological defense mechanisms. 23,37) CSE from the p50 strain of B. mori also inhibited the activity of bovine trypsin strongly, but it showed only very slight activity against bmCCN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are designated cocoon shell-associated trypsin inhibitors (CSTIs). 36) Although the physiological role of CSTI is not fully known, it has been suggested that it plays a significant role in biological defense mechanisms. 23,37) CSE from the p50 strain of B. mori also inhibited the activity of bovine trypsin strongly, but it showed only very slight activity against bmCCN.…”
Section: Discussionmentioning
confidence: 99%
“…36) Although the physiological role of CSTI is not fully known, it has been suggested that it plays a significant role in biological defense mechanisms. 23,37) CSE from the p50 strain of B. mori also inhibited the activity of bovine trypsin strongly, but it showed only very slight activity against bmCCN. Hence it is likely that a CSTI protects the cocoon from accidental proteolysis by extrinsic factors such as a protease from pathogenic bacteria, 37) and that upon eclosion CSTI does not interfere with the CCNcatalyzed proteolysis of sericin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, protease cocktails [54] and chymotrypsin (known to be produced by macrophages) are capable of enzymatically degrading silk [55]. Of interest, the silkworm B. mori produces a protease inhibitor in the silk gland embedding it within the silk cocoon for protection against premature proteolytic degradation [56].…”
Section: Silk Degradationmentioning
confidence: 99%
“…Recently bioactive compounds such as protease inhibitor polypeptides have been isolated from B. mori cocoons and their presence was shown to protect silk protein from proteolytic degradation. 4) In plants, ‰avonoids function as attractants of pollinators, 5) UV-protectants, 6,7) antimicrobial substances or phytoalexins, 8) and signaling molecules 9) in many species. Flavonoids in cocoon may thus be a protective agent and play an important role in protecting silk e.g.…”
mentioning
confidence: 99%